Pendidikan Nilai sebagai Suatu Strategi dalam Pembentukan Kepribadian Siswa - Dyah Kusuma Windrati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2011)
Value education serves to help students understand, appreciate, make the right decisions in a variety of personal problems, families, communities and countries that are expected to eliminate the arrogance that often occur. The value planting approaches (inculcation approach) is an approach that gives emphasis on the cultivation of social values in students. While the method used in this learning process are: Modeling, positive reinforcement, and negative, simulations, role games, etc. There are two views about the value. First, the value is the highest measure of human behavior and upheld by a group of people and used as guidance in attitude and behavior. Both values are dependent on fishing and feelings of people who are subject to certain phenomena. Value education methods that include: 1) method of advising (moralizing), 2) method of all to let 3) methods of model (modeling), 4) method of VCT (Value Clarification Technique). The concept of ideals in education according to Ki Hajar Dewantara main emphasis is ' ing ngarso sung tulodo' through ing ngarso sung tulodo educators showing they ideals in the form of behavior, speech, how to get along, deeds, scolds and so on.